Representasi Kemiskinan Dalam Film Turah - Utari Rachmawati; Ike Desi Florina; Inas Sany Muyassaroh (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
Representation of poverty in Turah movie explained through dialogue, language, symbol, image, expression which contain in the scene. Each scene in Turah movie is analyzed using Roland Barthes's semiotics, through denotation, connotation and myth as the process. This study method used a qualitative descriptive approach, with the aim of the research that is find out representation of poverty in "Turah" movie. The result of this study shows there is a representation of poverty in "Turah" movie which is shown through the scene in the movie. Based on the categorizations of poverty according to Chambers, those explain that poverty in "Turah" movie causes social problems, and as a result those social problems make Tirang villagers increasingly can not be released from the poverty.